Dari Eksklusifitas ke Inklusifitas: Pergeseran Pencurahan Roh dari PL ke PB Berdasarkan Yoel 2:28-29: Pergeseran Pencurahan Roh dari PL ke PB Berdasarkan Yoel 2:28-29 - Alexzander Parlindungan Manalu, Alex; Panggabean, Kristina A. M (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2025)
This research uses a literature study research method, with an exegesis approach. Exegesis will be conducted on the text of Joel 2:28-29 with the help of literature and book sources as well as theological journal articles related to this article. This article examines the outpouring of the Holy Spirit prophesied by Joel in Joel 2:28-29 and its impact on the paradigm of the spiritual life of the church today. The prophecy signaled a major shift in the way God reveals Himself to His people, from an exclusive outpouring of the Holy Spirit to an inclusive outpouring to all people, regardless of social status, gender, or age. Through this research, this article aims to discover and offer the theological implications of a more inclusive outpouring of the Holy Spirit to all believers, allowing every individual to participate in the ministry and mission of the church. Based on an analysis of the text of Joel and its application in the context of today's church, this article shows how the outpouring of the Holy Spirit changes the way the church views ministry, mission, and personal relationship with God.